Become a Sarmatian! The ways of attracting “citizens” to virtual states - Domaciuk-Czarny, Izabela (Papers in Linguistics, 2024)
The article discusses ways of attracting “citizens” to virtual states on the Internet, emphasizing the persuasive function of messages (both words and images) employed by the creators of these imaginary countries. Their goal is to invite and encourage followers to actively engage in the lives of their micronations. The creation of virtual nations and web-based micro-communities can be seen as a form of simulation games built on mimetic representation. This type of fiction primarily focuses on the constructed space, which, nevertheless, maintains ties with reality. The language utilized on these micro-nations’ websites is informal and familiar to the audience, and it includes an interesting selection of proper and common nouns as well as descriptions of fictional objects these nouns denote. The creators of such virtual countries strive to attract as many “citizens” as possible by capturing the attention of Internet users through the appeal of their micronation. They employ a wide array of linguistic and extralinguistic devices, such as calls to action (reminiscent of commercials), lexical evaluations, titles and distinctive reward systems, onymic wordformation, linguistic humour, the visual aspect of the project, and maps depicting the imaginary lands, etc.